2016
DOI: 10.3892/ijo.2016.3693
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of IR-780 dye-conjugated abiraterone for prostate cancer imaging and therapy

Abstract: Near-infrared fluorescence (NIRF) imaging is a novel imaging modality that allows for detection and real‑time monitoring of various pathophysiological states. IR-780 iodide has been used as an ideal platform to construct theranostic agents for cancer imaging and therapy. Abiraterone is a 17α‑hydroxylase/C17, 20‑lyase (CYP17) inhibitor that has been approved for use in patients with prostate cancer after androgen deprivation therapy. We report the synthesis and characterization of IR-780 conjugated abiraterone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 29 publications
2
11
0
Order By: Relevance
“…We choose this dye because it emits in the near infrared and can be easily detected by the in vivo imaging systems (IVIS), also avoiding background noise caused by the mouse's own autofluorescence. 76 When tumors reached a size of 0.5 cm 3 , 100 μL of O 2 LNC-i780, and αCD44-O 2 LNC-i780 were administered in the tail vein of the mice in a single dose. After one week, the mice were analyzed, euthanized, and the tumors were removed as well as all the organs.…”
Section: Lnc Sample (Figures S5−s15)supporting
confidence: 89%
“…We choose this dye because it emits in the near infrared and can be easily detected by the in vivo imaging systems (IVIS), also avoiding background noise caused by the mouse's own autofluorescence. 76 When tumors reached a size of 0.5 cm 3 , 100 μL of O 2 LNC-i780, and αCD44-O 2 LNC-i780 were administered in the tail vein of the mice in a single dose. After one week, the mice were analyzed, euthanized, and the tumors were removed as well as all the organs.…”
Section: Lnc Sample (Figures S5−s15)supporting
confidence: 89%
“…The 7-OH MOM-protected genistein was then selectively conjugated through the 4′-OH with IR 783. HCD, IR 783 is known to have high affinity with cancer cells and is now under extensive investigation from mechanistic to drug-carrying abilities [21,22,31,36,44]. As shown in Scheme 1 the desired conjugate was obtained as single isomer upon MOM group deprotection and characterized by 1 H-NMR and mass spectrometry for the chemical composition (see Supplementary Materials).…”
Section: Discussionmentioning
confidence: 99%
“…We recently demonstrated that radiolabeled cyanine dye molecules can be used to detect and diagnose cancer lesions [24,25]. Additional reports of cancer cell-specific delivery and targeting of drug-cyanine dye conjugates to tumors have been described by us and other laboratories [26,27,28,29,30,31,32]. Considering ongoing research on genistein in our laboratory [33], we sought to improve its therapeutic potential by conjugating it with a cyanine dye.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, this dye is known to selectively accumulate in cancer cells and has been used to discriminate between tumor lesions from normal tissues (Zhang et al, 2014). Yi et al recently described on a novel IR780-abiraterone conjugate ( 2 , Figure 3) for the concomitant imaging and therapy of PC both in vitro and in vivo (Yi et al, 2016).…”
Section: Molecular Conjugates For Pdt-mediated Pc Treatmentmentioning
confidence: 99%